Basic and clinical andrology (BioMed Central, 2013)
"Basic and Clinical Andrology is an open access journal in the domain of andrology covering all aspects of male reproductive and sexual health in both human and animal models. The journal aims to bring to light the various clinical advancements and research developments in andrology from the international community."